Model Problem Based Learning: Efektivitasnya Dalam Meningkatkan Hasil Belajar Sistem Persamaan Linear Dua Variabel - Hendro Budi Santoso; Lailany Yahya; Dewi Rahmawaty Isa (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2023)
This research is classroom action research. This study aims to improve student learning outcomes in the material system of two-variable linear equations. This research was conducted in class VIII SMP Negeri 3 Satap Tabongo, with 17 students as research subjects. Data collection is done by using observation and tests. Data analysis was carried out by looking at the average results of students who passed and the results of observations that reached the minimum good criteria. This research lasted for two cycles with results in the form of observations of teacher activities that increased from 73% to 88.5% in the good and very good categories. Furthermore, the results of student activities increased from 61.25 to 92% in the good and very good categories. As well as learning outcomes also increased from 58.82% to 88.2%. By looking at these results, it can be concluded that the Problem-Based Learning model can improve student learning outcomes in the matter of a two-variable linear equation system in class VIII SMP Negeri 3 Satap Tabongo.